SMEs entry mode choice : Finnish clean-tech companies in China - Wang, Wei (2018)
Entry mode selection process is a profound step in firm’s international activities. Despite the increasing prevalence of study on this issue, many research questions on SMEs (Small and medium-sized enterprises) remain open. Given SMEs play a prominent role in world economy, a better understanding on their entry mode selection process is needed for academy and managers. Rise of Finnish cleantech SMEs and huge market potential of Chinese market drive the market-orientated motivation of this thesis. The aim of this thesis is to explore the decision-making process on entry mode selection in Finnish cleantech SMEs heading into Chinese market. This thesis, employing transaction cost theory as theoretical ground and qualitative case study as research method, examines three Finnish cleantech companies to draw out the patterns of their decision-making process and one Finnish organization to observe the work from a third-party angel. Assets specificity, internal uncertainty and external uncertainty from transaction cost theory are the three key dimensionalities in analysis work of the case companies’ entry mode selections and performances. Second-hand information and working experience of author have also greatly assisted in the process. The primary findings of this thesis are: 1. Assets specificity, especially characteristics and the customized of products or service, scopes the preliminary entry mode options which are all related to local collaboration. Local collaboration is an effective means for SMEs to release their dilemma of resource restraint. 2. International experience and intensive working experience in target country of managers or top management team can reduce bias, distrust and uncertainty from decision makers as natural human beings. 3. Deep analysis of external environment is neglected but shall penetrate into actual industry environment, target customer behaviors, relative policies from government and competition situation. Through that, possible project opportunity can be allocated and detailed strategy can be justified and sharpen. Further research is recommended to assess the relationship between firm’s selected entry mode made based on transaction cost theory and performance in a longer time scope from process perspective and extended into other high-tech industry.